New Common Agricultural Policy of the European Union (2023-27) and Potential Implications on Serbian Agriculture - Jović, Luna Vodana; Đokić, Danilo; Zekić, Stanislav (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
In the last few years, significant changes have taken place in the agricultural policy of the European Union. First, in 2020, the Farm to Fork Strategy was presented as part of the broader European Green Deal strategy adopted a year earlier. The main idea of ??this strategy is to redesign the European food system, which has a significant impact on global climate change. It is estimated that almost one-third of global greenhouse gas emissions come from agri-food systems. In addition, these systems use vast amounts of natural resources (primarily water and land), resulting in biodiversity loss. This strategy has contributed to redefining the European Union’s Common Agrarian Policy for the period from 2023 to 2027. The Agreement on the Reform of the Common Agrarian Policy was officially adopted on December 2, 2021. One of the critical elements of this agreement is the protection of the environment and the idea of ??making the European Union’s agricultural policy "greener". Thus, a strong interdependence between the agricultural policy and the European Green Agreement has been created. On the other hand, Serbia is in the process of European integration, which includes harmonization with the Common Agricultural Policy. Therefore, the new reform of the Common Agricultural Policy and the Farm to Fork Strategy could be significant for the development of the agricultural policy of Serbia with substantial consequences for the agri-food sector. This paper aims to present new trends in European policy in the food sector and point out the potential implications for the agricultural sector of Serbia.